A heuristic optimisation algorithm for two-echelon (R, Q) inventory systems with non-identical retailers. (2016) - Al-Rifai, Mohammad H.; Rossetti, Manuel D.; Sheikhzadeh, Alireza
This paper describes an optimisation algorithm that minimises the total inventory investment of a one warehouse and an m non-identical retailer's inventory system using reorder point and order quantity (R, Q) policies. The inventory system is subject to constraints on the average ordering frequency and number of backorders. The system is decomposed by echelon and location, and analytical expressions are derived for the inventory policy parameters. Sets of computational experiments illustrate the effectiveness of the heuristic over a wide range of problem instances. Experimental results indicate that the heuristic optimisation algorithm is an effective procedure for optimising the sampled inventory systems regarding both the quality of the solutions and the computational times. This research provides approximations and a heuristic optimisation procedure for a two-echelon inventory system for the non-identical retailer's case.